Voltage-mode biquad filter using three lt1228s with independent and electronic control of center frequency and quality factor - Wai, May Phu Pwint; Jaikla, Winai; Chaichana, Amornchai; Suwanjan, Peerawut; Chanapromma, Chaiyan; Sunthonkanokpong, Wisuit (My University, 2023)
In this paper, we describe a voltage-mode (VM) biquad universal filter with one input and four outputs that can be tuned electronically. The filter proposed here is composed of three LT1228 commercial integrated circuits (ICs), seven resistors and two grounded capacitors. The proposed versatile biquad filter simultaneously provides four filtering functions: An inverting low-pass filter (LP), an inverting high-pass filter (HP), a non-inverting bandpass filter (BP), and an inverting notch filter (BR) without changing its topology. Employing two grounded capacitors minimizes the influence of parasitic resistances and capacitances on the proposed circuit's performance. Also, the output voltage nodes of the HP and BR functions have low output impedances. This means that these two filtering functions don't need voltage buffers to connect to other voltage-mode topologies. The center frequency (ω0) of the presented filter is electronically controlled and does not influence the quality factor (Q). In addition, they can also be tuned linearly without affecting each other. PSPICE software was used to analyze the modelling results, while a laboratory experiment was performed using LT1228 commercial ICs.
Keywords: Biquad filter; Electronic control; Independent controllability; LT1228; Voltage-mode circuit This work was supported in part by King Mongkut’s Institute of Technology Ladkrabang (KMITL)